Marxism through time - Nemenzo, Francisco 1935- (Quezon City U.P. Diliman Interactive Learning Center, 2005)
The first of a series of four lectures on Social Science II: a general education course on the social, economic and political thought.
Lecture delivered on September 8, 2004.
Executive producer, Celia T. Adriano ; Director, Gigi Javier-Alfonso ; Co-produced by, U.P. Computer Center, U.P. Open University Media Center, Department of Electrical and Electronics Engineering, College of Engineering.
Series Lecturer: Francisco Nemenzo ; Moderator/Narrator: Malaya C. Ronas.
Keywords: Marx, Karl -- 1818-1883 -- Congresses; Marx, Karl -- 1818-1883 -- Congresses. -- Political and social views; Communism -- Congresses; Communist revisionism -- Congresses; Capitalism -- Congresses; Socialism -- Congresses; Industrial revolution -- Congresses